Structural Competence. Issue 5 (September 2020) - Wisner, Kirsten
Abstract : Perinatal nurses can tailor care and supportive strategies by maintaining cultural competence, practicing cultural humility, and probing for structural barriers and risk factors inherent in each patient's unique situation. Our maternity nursing expert, Dr. Wisner, explains how to integrate these concepts in clinical practice.